2015
DOI: 10.1111/jiec.12219
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Life Cycle Assessment of a Canned Sardine Product from Portugal

Abstract: SummaryThis study aims to assess the environmental impacts of canned sardines in olive oil, by considering fishing, processing, and packaging, using life cycle assessment (LCA) methodology. The case study concerns a product of a canning factory based in Portugal and packed in aluminum cans. It is the first LCA of a processed seafood product made with the traditional canning method. The production of both cans and olive oil are the most important process in the considered impact categories. The production of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 29 publications
(64 reference statements)
4
37
0
Order By: Relevance
“…Construction, structural maintenance and especially EOL are systematically excluded in processed seafood LCA literature (Hospido et al 2006;Iribarren et al 2010;Vázquez-Rowe et al 2014;Almeida et al 2015) and fisheries LCA literature (Avadí and Fréon 2013) under the assumption that their contributions to overall impacts are negligible. In a very fuel-efficient fishery, however, construction and structural maintenance may have non-negligible contributions Fréon et al 2014a); thus, we prophylactically included these life cycle phases for the fishery, and the construction phase for the tuna processing plant (the latter to confirm or deny its perceived negligibility).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Construction, structural maintenance and especially EOL are systematically excluded in processed seafood LCA literature (Hospido et al 2006;Iribarren et al 2010;Vázquez-Rowe et al 2014;Almeida et al 2015) and fisheries LCA literature (Avadí and Fréon 2013) under the assumption that their contributions to overall impacts are negligible. In a very fuel-efficient fishery, however, construction and structural maintenance may have non-negligible contributions Fréon et al 2014a); thus, we prophylactically included these life cycle phases for the fishery, and the construction phase for the tuna processing plant (the latter to confirm or deny its perceived negligibility).…”
Section: Methodsmentioning
confidence: 99%
“…A carbon footprint analysis of Thai tuna canning, based on a fuel-intensive tuna fishery, also identified the provision of raw materials, tinplate cans and process energy as the main drivers of global warming potential (climate change) (Mungkung et al 2012). A recent study of canned sardine from Portugal (Almeida et al 2015), supplied by a fishery with a FUI of 111-113 L/t (Almeida et al 2013), also identified the provision of (aluminium) cans as the main contributor to most impact categories. Another recent study on Peruvian anchoveta processing ) confirms this trend and, moreover, identifies potentials for reducing impacts of fish packaging by favouring pouches or at least larger cans.…”
Section: Life Cycle Impact Assessmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Their normalised results are shown in rows 7 to 10 in Table 2. As previously discussed, changing the packaging material is one of the variables that influences the most the environmental performance of the process (Almeida et al 2015;Hospido et al 2006). However, there is no solution that scores better than the rest for every metric.…”
Section: Packaging Materialsmentioning
confidence: 99%
“…Aluminium and tinplate cans as well as glass jars are already employed in the Cantabrian factory. Furthermore, it is interesting to study other possible materials such as plastic, which is already used by a Danish company as the usual canned appearance(Almeida et al 2015). Four different scenarios are thus distinguished for the assessment of the packaging material: aluminium (SG), tinplate (SH), glass (SI) and plastic (SJ).…”
mentioning
confidence: 99%